A histological evaluation of pansteatitis‐affected Mozambique tilapia, Oreochromis mossambicus (Peters 1852), from different geographical locations in South Africa. Issue 10 (1st August 2020) - Sara, Joseph R.; Luus‐Powell, Wilmien J.; Fogelson, Susan B.; Botha, Hannes; Guillette, Theresa C.; Smit, Willem J.; Hoffman, Andre; Kunutu, Katlego D.; Koelmel, Jeremy P.; Bowden, John A.
Abstract: Pansteatitis is the leading cause for the decline in Nile crocodile populations and the sporadic mortality of fish in the Olifants River System, South Africa. To determine the prevalence of this disease in lentic systems, Mozambique tilapia, Oreochromis mossambicus, were collected from Lake Loskop, Lake Flag Boshielo, Phalaborwa Barrage and Lake Luphephe‐Nwanedi. The former three impoundments are located within the main stem of the Olifants River, while the latter, which is geographically isolated and situated in the Limpopo River System, served as a reference site. Mesenteric adipose, liver, serosa of the swim bladder, gill and the skeletal muscle of fish sampled were examined for gross and microscopic evidence of pansteatitis. Microscopically observed changes were used to statistically compare pansteatitis prevalence between samples and sites. Based on histopathological evaluation, the adipose tissue in the liver, swim bladder serosa and coelom from severely debilitated individuals showed the most significant pathological changes. Lesions indicative of steatitis were observed in fish collected from Lake Loskop (75%), Lake Flag Boshielo (22%) and Lake Luphephe‐Nwanedi (15%). Further investigation is warranted to understand the pervasiveness and mechanisms driving pathological changes of pansteatitis at Lake Flag Boshielo, Phalaborwa Barrage and Lake Luphephe‐Nwanedi.